Effect of plasminogen activator inhibitor-1 and tissue plasminogen activator polymorphisms on susceptibility to type 2 diabetes in malaysian subjects - Al-Hamodi, Z.; Saif-Ali, R.; Ismail, I.S.; Ahmed, K.A.; Muniandy, S. (2012)
Elevated activity of plasminogen activator inhibitor-1 (PAI-1) and decreased tissue plasminogen activator (tPA) activity are considered to be important risk factors for type 2 diabetes mellitus (T2DM) and metabolic syndrome (MetS). The aim of this study was to investigate the association of the PAI-1 4G/5G and tPA Alu-repeat I/D polymorphisms with T2DM in Malaysian subjects. Serum insulin, coronary risk panel, plasma glucose, and PAI-1 4G/5G and tPA Alu-repeat I/D polymorphisms were studied in 303 T2DM subjects (227 with MetS and 76 without MetS) and 131 normal subjects without diabetes and MetS. Statistical analysis showed that the dominant and additive models of PAI-1 4G/5G polymorphism showed a weak association with T2DM without MetS (OR = 2.35, P = 0.045; OR = 1.67, P = 0.058). On the other hand, the recessive model of the tPA Alu-repeat I/D polymorphism showed an association with T2DM with MetS (OR = 3.32, P = 0.013) whereas the dominant and additive models of the tPA Alu-repeat I/D polymorphism were not associated with T2DM either with or without MetS.